HIV/AIDS: STIGMA AND DISCRIMINATION-LIVE AND LET LIVE - Siddiqui, Noaman (Journal of Ayub Medical College Abbottabad, 2002)
At the end of the year 2002, there were over 3 million deaths and 42 million people suffering from HIV/AIDS. Since its identification, HIV/AIDS has been associated with social responses of fear, denial, stigma and discrimination. It is as important to find medical cure for the illness as is the combating of the stigma, discrimination and denial of human rights to the unfortunate people affected by HIV/AIDS. This illness will have to be accepted as a disease and not a punishment as epilepsy, tuberculosis and leprosy have been in the past. If this is not done there is no hope to harness and eventually rid human kind of this tragedy of a pandemic proportion. World AIDS Campaign 2002-2003 focuses on stigma, discrimination and denial of human rights and aims at fighting these dangerous attitudes through its slogan ’Live and Let Live’. Stigmatization leads to devaluating and discrediting an individual. This leads to denial of human rights. All these are inter-linked and reflect the credibility of a nation. Women throughout the world are subjected to stigma as women, as HIV-positive women and as HIV-positive women who are pregnant. Stigma was reported everywhere to be more extensively directed against women than against men. Stigma surrounding mother-to-child transmission (MTCT) prevents women coming forward for testing, reduces their choices in terms of health care and family life once they are known to be HIV-positive, and negatively impacts on their quality of life. People with or suspected of having HIV/AIDS should no longer be turned away from healthcare services, employment and entry to foreign counties. They should no longer be evicted from homes by their families, rejected by their friends, schoolmates and colleagues. The individuals suffering from HIV/AIDS should not be automatically considered as sinful or evil as they are worthy of sympathy like any person suffering from whatever the illness. It must be made clear that HIV/AIDS is not only a disease of homosexuals, prostitutes, drug addicts, sinners or persons punished by God but also affects the newborn, a feeding infant and innocent recipient of blood transfusion. The fear of being discriminated in selection for education and employment; respect within family or society; being punished rather than treated leads to denial of disease and seeking treatment or investigation. This flares and spreads the illness like an unchecked jungle fire with equally devastating results. If this fire has to be effectively extinguished, the fire fighting team must include every member of the society and not just the healthcare workers. Recommendations include reduction of impact of stigma in general. Strengthening the legal framework to protect the human rights of people with HIV/AIDS is of paramount importance. Supportive environment should be to reduce stigma through national and community-based communication initiatives to combat fear and misinformation; to improve community based services for people living with HIV/AIDS; and to increase accessibility to affordable antiretroviral (ARV) therapy. The team workers should remove all prejudices and discriminations against HIV/AIDS sufferers and must comprise of educationists, clergy, media personnel, lawyers, youth etc. They should carry a strong message Fight AIDS not people with AIDS.